Female misrepresentation in selected peripheral pieces: glimpsing into Native Son, Beauty is a Wound and The Lonely Londoners - Arna, Nusrat Tasnim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.